High‐fat diet prevents the development of autoimmune diabetes in NOD mice. Issue 11 (2nd August 2021) - Clark, Amy L.; Yan, Zihan; Chen, Sophia X.; Shi, Victoria; Kulkarni, Devesha H.; Diwan, Abhinav; Remedi, Maria S.
Abstract: Aims: Type 1 diabetes (T1D) has a strong genetic predisposition and requires an environmental trigger to initiate the beta‐cell autoimmune destruction. The rate of childhood obesity has risen in parallel to the proportion of T1D, suggesting high‐fat diet (HFD)/obesity as potential environmental triggers for autoimmune diabetes. To explore this, non‐obese diabetic (NOD) mice were subjected to HFD and monitored for the development of diabetes, insulitis and beta‐cell stress. Materials and Methods: Four‐week‐old female NOD mice were placed on HFD (HFD‐NOD) or standard chow‐diet. Blood glucose was monitored weekly up to 40 weeks of age, and glucose‐ and insulin‐tolerance tests performed at 4, 10 and 15 weeks. Pancreata and islets were analysed for insulin secretion, beta‐cell mass, inflammation, insulitis and endoplasmic reticulum stress markers. Immune cell levels were measured in islets and spleens. Stool microbiome was analysed at age 4, 8 and 25 weeks. Results: At early ages, HFD‐NOD mice showed a significant increase in body weight, glucose intolerance and insulin resistance; but paradoxically, they were protected from developing diabetes. This was accompanied by increased insulin secretion and beta‐cell mass, decreased insulitis, increased splenic T‐regulatory cells and altered stool microbiome. Conclusions: This study shows that HFD protects NOD mice from autoimmune diabetes and preserves beta‐cell mass and function through alterations in gut microbiome, increased T‐regulatory cells and decreased insulitis. Further studies into the exact mechanism of HFD‐mediated prevention of diabetes in NOD mice could potentially lead to interventions to prevent or delay T1D development in humans.